1955
DOI: 10.1172/jci103160
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamics, Sodium and Water Excretion in Supine Exercising Normal and Cardiac Patients 1

Abstract: Diminished sodium excretion is one of the factors underlying edema formation in congestive heart failure. The clinical improvement and disappearance of the edema in some cardiac patients treated with bed rest alone suggests the importance of exercise as a potentiating factor in the sodium retention. Exercise studies carried out in normal and cardiac patients in the upright position by other investigators are open to question since the upright position itself is a factor in diminished sodium excretion. In order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1959
1959
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The mean calculated renal blood flow during moderate exercise was 20% of the normal resting value. These figures are in remarkable agreement with renal blood flow measurements during exercise in patients with heart disease by other workers using renal clearance techniques (Aas and Blegan, 1949;Freeman et al, 1955;Judson et al, 1955;Werkd et al, 1954). The only important advantage of our technique is that it allows immediate changes of flow to be studied in a manner not possible with the renal clearance methods.…”
Section: Kidneysupporting
confidence: 89%
See 1 more Smart Citation
“…The mean calculated renal blood flow during moderate exercise was 20% of the normal resting value. These figures are in remarkable agreement with renal blood flow measurements during exercise in patients with heart disease by other workers using renal clearance techniques (Aas and Blegan, 1949;Freeman et al, 1955;Judson et al, 1955;Werkd et al, 1954). The only important advantage of our technique is that it allows immediate changes of flow to be studied in a manner not possible with the renal clearance methods.…”
Section: Kidneysupporting
confidence: 89%
“…persons, but that it is to a lesser degree for a given exertion than in patients with severe heart disease (Freeman et al, 1955) and presumably restricted cardiac outputs. Brain The next regional circulation to be studied during leg exercise was that of the brain .…”
Section: Kidneymentioning
confidence: 99%
“…Bucht et al (1953) found no change in renal blood flow during light exercise in the supine position, but it decreased during very heavy exercise. Freeman et al ( 1955) found that the bladder clearance of PPaH was unchanged during very severe excrcise of short duration in the supine position. In the above four experimei~ts renal blood flow was measured with the subject in the supine position and did not decrease during exercise.…”
Section: Rerzal Blood Flowmentioning
confidence: 84%
“…persons, but that it is to a lesser degree for a given exertion than in patients with severe heart disease (Freeman et al, 1955) and presumably restricted cardiac outputs.…”
Section: H13mentioning
confidence: 99%